Transforming Worker Representation: The Magna Model in Canada and Mexico - Lewchuk, Wayne; Wells, Don (Labour/Le Travailleur, 2007)
Abstract The emergence of internationalized production in the context of weakening state regulation of labour rights and of increasing employer dominance in industrial relations systems raises significant questions about the nature and future of worker representation. A crucial issue is the transferability of company-specific models of worker voice across national boundaries. This issue is the focus of this case study of Magna International, a leading member of a small group of transnational automotive parts manufacturing firms that are central to the contemporary restructuring of the international automotive industry. The paper compares the transformation of worker representation at Magna in Canada and Mexico. In crossing international borders, the Magna industrial relations model has taken on national and local features of the host country. However, the underlying industrial relations structure is one which has elicited a successful reconfiguration and containment of much, although by no means all, of the adversarialism inherent in labour-management relations. This reconfiguration has aligned worker representation to an essentially unitarist project oriented to management’s productivity goals. More than merely suppressing independent unions, Magna has constructed a coherent, management-dominated model of worker representation in both Canada and Mexico. The paper concludes with an assessment of the implications of this model for independent unionism.